2012
DOI: 10.1177/0194599812464020
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Adenoid Cystic Carcinoma

Abstract: This study contains the largest pool of SNACC patients to date. The data suggest that SNACC has a poor overall prognosis. It also suggests that surgery with postoperative radiotherapy is the most commonly used and may possibly be the most effective therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 116 publications
0
25
0
Order By: Relevance
“…The prognostic effects of solid histopathology are controversial. Some believes it means a lower rate of survival when compared with the tubular or cribriform type, whereas others have shown that there is no relationship [46, 47]. The combined analysis showed that the recurrence rate of patients with positive expression of p53 was 43.1%, and that of patients with negative expression of p53 was 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic effects of solid histopathology are controversial. Some believes it means a lower rate of survival when compared with the tubular or cribriform type, whereas others have shown that there is no relationship [46, 47]. The combined analysis showed that the recurrence rate of patients with positive expression of p53 was 43.1%, and that of patients with negative expression of p53 was 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Upon presentation, SNACC frequently involves local vital structures such as orbit, cranial nerves, brain, dura and carotid arteries, limiting the option for aggressive surgery . Because of its tendency to present in an advanced stage, surgery with adjuvant radiotherapy has been the mainstay of treatment for SNACC . However, studies assessing the most effective treatment modalities for SNACC have presented contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review consisting of both individual and aggregate SNACC patient data reported a 5-year survival rate of 62.5%. 22 A retrospective cohort study using the United States National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) registry identified a total of 412 cases between 1973 and 2009. The 5-year OS rate was 68.8% with African Americans having inferior survival compared to other races, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%